Membangun Akhlak dan Disiplin dalam Belajar: Telaah Literatur Kitab Ta’lim Muta’alim - Andi Abd. Muis; Mardiati M; Nursia Nursia; Yenni Yenni; Rudi Hartono; Zulbina Zulbina; Nur Aisyah (FKIP UNSULTRA, 2025)
Learning emphasizes not only mastery of knowledge, but also the formation of morals and discipline as the foundation of student character. The Ta'lim Muta'alim book is one of the classic references that outlines the ethical principles of seeking knowledge and strategies for developing learning discipline. This study aims to analyze the moral and disciplinary teachings contained in the book and their relevance in the context of modern education. The research method used is a literature study with a descriptive-analytical approach, through the identification, classification, and interpretation of the Ta'lim Muta'alim text. The analysis results show that this book emphasizes several main principles, namely sincere intentions, sincerity in learning, respect for teachers, patience, and consistency in learning practices. In addition, this book teaches the importance of time management, maintaining focus, and establishing a disciplined learning routine. The moral values ​​taught, such as honesty, humility, and a sense of responsibility, not only shape moral character but also increase learning effectiveness. These findings indicate that the classical principles in Ta'lim Muta'alim remain relevant for application in contemporary education, both in schools and in independent learning. Implementing these teachings can strengthen students' learning discipline and foster ethical behavior that supports academic success and character development. This study concludes that integrating morals and discipline into the learning process is key to developing a competent, responsible, and noble generation.